ORGANIZING RETURN MIGRANT WORKERS FROM INDONESIA FOR SUSTAINABLE GOVERNANCE - Meiliyana, Meiliyana (STISIPOL Dharma Wacana, 2019)
Artikel ini akan menyajikan pemahaman tentang bagaiamana purna buruh migrant dapat memberikan dampak bagi keluarga dan masyarakat di sekelilingnya dalam hal peningkatan kualitas hidup dan kesejahteraan. Latar belakang utama dari artikel ini adalah semakin mudah dan banyaknya orang yang memutuskan menjadi pekerja migran di luar negaranya sebagai dampak dari globalisasi. Selanjutnya artikel ini akan focus pada purnaburuhmigran dan akan mencoba memberikan penjelasan pentingnya penelitian lebih lanjut tentang bagaimana para purna buruh migrant tersebut dapat berkontribusi untuk pembangunan yang berkelanjutan. Dalam artikel ini disajikan beberapa hasil penelitian tentang hubungan remitan, pembangunan dan buruh migran di dua negara Asia Tenggara yang merupakan negara pengirim buruh migrant terbesar di asiaTenggara. This article presents an understanding of how returnees of overseas workers have an impact on family and community in term of prosperity and wellbeing. The main background of thisarticle is the growing trend of migration as one impact of globalization. Furthermore this article focuses on overseas workers and will seek to address the lack attention of current research on demonstrating how returnees overseas workers could contribute to sustainable development. At the end of the article it suggests to do further research in order to find answers about the impacts of having experiences as overseas workers for family and community prosperity and well being. In this article is discussed two regions in Southeast Asia namely Indonesia and Philippine where in these two countries playing significant role as sending countries for overseas workers.